A new (propylphenyl)bibenzyl derivative from Dendrobium williamsonii. Issue 14 (18th July 2018) - Yang, Miao; Zhang, Yan; Chen, Lijun; Chen, Yegao
Abstract: A new (propylphenyl)bibenzyl derivative, dendrowillol A (1 ), along with 22 known compounds were isolated from the whole plants of Dendrobium williamsonii . Their structures were elucidated by means of extensive spectroscopic analysis. Cytotoxicity evaluation against five human tumour lines showed that all the compounds tested displayed very weak cytotoxicity when compared with the positive control taxol, but selective inhibitory effects on HL-60 for several compounds tested were observed, with IC50 values ranging from 4.48 to 11.04 μM. Abstract :